The Economic Impact of the 2014 Ebola Epidemic : Short- and Medium-Term Estimates for West Africa - World Bank Group (Washington, DC: World Bank, 2014)
Beyond the terrible toll in human lives and suffering, the Ebola epidemic currently afflicting West Africa is already having a measurable economic impact in terms of forgone output; higher fiscal deficits; rising prices; lower real household incomes and greater poverty. These economic impacts include the costs of healthcare and forgone productivity of those directly affected but, more importantly, they arise from choices by others to avoid exposure to the disease, called 'aversion behavior'. This report provides a systematic analysis of the channels of economic impact and the likely magnitude of that impact for Guinea, Liberia, and Sierra Leone, as well as West Africa as a whole.